IMPLEMENTASI APLIKASI MOBILE E – MAGAZINE BERBASIS ANDROID - Mega Rista; Sondang Dasawaty (Jurnal Informatika dan Bisnis, 2015)
Even it looks like not important entertainment have an important role for human life. Along with information technology development, magazine not only printed in book dan tabloid form, but also in electronic or online. E-Magazine is an electronic magazine made with Java programming language to Android application and PHP programming language to its web application. The goal of this research is to made a perfect electronic magazine to reader so they can get information that they need and entertainment from their smart phone. In this research, requirements and data gathered by observation non participant from another e – magazine that already published in Indonesia and from relevant literature and books also article in library. And in the end, the result of this reasearch is an electronic magazine that can be run on Android phone so it gives an easy access for reader to read their favorite magazine whereever they want. The summarize of this research are not only fill out with writing article but also image to support the article and its automatic delivery by system make this electronic magazine more economical.